1996
DOI: 10.1038/sc.1996.130
|View full text |Cite
|
Sign up to set email alerts
|

An atypical presentation of tuberculosis of the spine

Abstract: We present a retrospective analysis of 684 patients operated on for a herniated lumbar intervertebral disc. Of the 87 patients with a failed back syndrome, 12 were confirmed to have tuberculous infection of the same disc interval. These patients responded satisfactorily to bracing and a short course of anti-tubercular chemotherapy. Histopathological confirmation of the disease was obtained by CT guided biopsy, and only a few of the patients required repeat surgery. This study highlights one of the atypical pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…Our findings are in agreement with those of Pande et al. who reported that in 87 patients with ‘failed back syndrome’, 12 were confirmed to have tuberculous discitis [20]. Galukande et al.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are in agreement with those of Pande et al. who reported that in 87 patients with ‘failed back syndrome’, 12 were confirmed to have tuberculous discitis [20]. Galukande et al.…”
Section: Discussionsupporting
confidence: 94%
“…The findings of this study indicate that TB is a common cause of LBP in our population. Our findings are in agreement with those of Pande et al who reported that in 87 patients with 'failed back syndrome', 12 were confirmed to have tuberculous discitis [20]. Galukande et al also reported that in patients with LBP, a significant percentage had spinal pathology caused by tuberculosis [21].…”
Section: Discussionsupporting
confidence: 93%
“…Atypical features that were described in the previous reports are 1) involvement of the spinal posterior element with a sparing of the anterior column; 2) skip lesions; and 3) neural component compression as a result of tuberculosis granuloma4. The most common site of involvement of the posterior element of the spine is the pedicle1.…”
Section: Discussionmentioning
confidence: 93%
“…S pinal tuberculosis in its classical form (i.e., two-vertebra disease with destruction of the intervening intervertebral disk and a paravertebral or psoas abscess) is easily recognized and readily treated in areas where tuberculosis is endemic [1][2][3][4] . Atypical spinal tuberculosis without the aforementioned clinical or radiographic features 5 , although occurring less frequently 6 , has been well documented [6][7][8] . However, only a few articles have reported isolated tuberculosis involving a single vertebral body 1,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few articles have reported isolated tuberculosis involving a single vertebral body 1,9,10 . Single vertebra tuberculosis presenting with a localized, solitary, osteolytic lesion without collapse of vertebral body is exceedingly rare and there is limited information about this entity in English-language published reports 1,2,[5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%